INFLUENCE OF PROJECT METHODS ON LEARNERS' LEARNING OUTCOMES IN DRAMA COURSES IN PANDEMIC ERA - Tamaela Ida Costansa; Marshalo Rovianto Kakerissa; Windy Putri Latuheru (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2022)
The purpose of this study is to describe the effectiveness of project methods in pandemic times in drama courses in the German Language Education Study Program. The respondents in the study were fifth-semester students. The project phase in this research consists of 7 phases, namely: 1) Preparation phase (Vorbereitungsphase); 2) Early phasel (Einstiegsphase); 3) Planning phase (Planungsphase); 4) Implementation and realization phases (Ausführungsphase). 5) Evaluation and control phase (Auswertungsphase); 6) Final Results Phase (Ergebnis präsentation), and 7. Closing phase (Abschluss). According to Reich, K: Data collection techniques using qualitative descriptive methods. The end result of the project is to create a picture book about Maluku folklore (Mӓrchen). Maluku folklore book is made following the script of the drama from Esser Rolf, namely: The beginning, conflict situation, climax, redah, and end. The final results of the project showed 4 respondents got a score of 70, 3 respondents got a score of : 80, 7 respondents got a score of 90, and 3 respondents got a score of 100. Based on the assessment score of the final results of learning, it can be concluded that the project method has a positive influence on the learning outcomes of Drama courses